Produção de massa de forragem, de leite e de grãos em sistema de integração lavoura-pecuária - Krutzmann, Alexandre (2011)
The experiment was carried out in northwestern of Paraná State, in the city of Santo Inácio. The objective was to evaluate the implementation of tropical forage grasses in the system of crop-livestock integration and their effect on the accumulation and morphological composition of forage mass, dry mass and chemical composition of available forage even as the animal production. It was evaluated the vegetation cover and nutrient accumulation in straws from grasses as well as the behavior of the soybean crop in this integrated system implemented in the period between February 2009 and February 2010. It was used an experimental design of randomized blocks with split plot in time with two replicates and three treatments. The experimental field comprised an area of six hectares. The main treatments were: Brachiaria ruziziensis + Panicum maximum Jacq. cv. Tanzania-1 planted overseeded; Brachiaria ruziziensis + Panicum maximum Jacq. cv. Tanzania-1, in line planting; Brachiaria brizantha cv. Marandu + Panicum maximum Jacq. cv. Tanzania-1 in line planting, being evaluated in the subplot the cutting periods. The experimental area had been worked since the year of 2003, under the no-tillage system, receiving during the winter the sowing of tropical and temperate grasses and in the summer the soybean crop. For pasture management it was used the method of continuous stocking with variable stocking rate, keeping the same height of 30 cm. To maintain the height and forages management there were used Holstein-Zebu crossbred cows, with initial average weight of 470 kg of live weight (LW), using four testers animals per paddock. For the estimation of forage production, morphological components and chemical composition, samples were collected every 21 days. The assessment of animal production was performed in two stages during the experiment (08/23 and 09/25/2009), analyzing the milk production, as well as its chemical composition. The residual straw from pasture was evaluated 31 days after the end of the grazing, considering their production and morphological characteristics, as well as, the contents of the macronutrients nitrogen, calcium, phosphorus, potassium and magnesium that were in the same. The phithotechnical evaluation of soybean plant began with the establishment of the same on the system, making the initial stand, the other evaluations were realized with the end of the crop cycle, being evaluated the yield components and grain production. The productions of dry matter of herbage and leaf blades showed similarity between the treatments, with average values of 2,285 and 1,017 kg / ha, respectively. The daily accumulation of dry mass of forage grasses was not affected by periods of evaluation and treatments, with an average of 69.64 kg / ha. The method of overseeding of Marandu grass and B. ruziziensis sown in the R7 stage of soybean crop can be used in the implementation of pasture in system of crop-livestock integration. These grasses had similar values in their chemical composition and in vitro digestibility, so the leaf fractions had an average protein content, neutral detergent fiber and in vitro digestibility of 13.07%, 58.68% and 58.95%, respectively. Similarly, milk production did not differ between treatments, with mean values of 9.13 kg /cow/day, as well as its chemical composition, which showed respectively the mean levels of fat and protein 3.30% and 3.20%. Holstein x Zebu crossbred cows with milk production potential of up to 10 kg per day can be managed in pastures of B. ruziziensis and Marandu grass intercropped with Tanzania grass, when planted in system of crop-livestock integration, with a stocking rate of 3.69 AU / ha. The residual straw from pasture showed similarity with respect to dry matter production between treatments, with a mean value of 2,856.1 kg / ha. Calcium and nitrogen are the nutrients accumulated in larger amount in vegetation cover from pasture of Marandu grass and B. ruziziensis intercropped with Tanzania grass. Yield components and grain productivity of soybean crop are not influenced by vegetation cover under soil from pastures of Brachiaria ruziziensis and brizantha cv. Marandu intercropped with Tanzania grass.